CD151 mediates netrin‐1‐induced angiogenesis through the Src‐FAK‐Paxillin pathway. Issue 1 (25th August 2016) - Yang, Xiaosheng; Li, Shiting; Zhong, Jun; Zhang, Wenchuan; Hua, Xuming; Li, Bin; Sun, Hui
Abstract: Crosstalk between the nervous and vascular systems is important during development and in response to injury, and the laminin‐like axonal guidance protein netrin‐1 has been studied for its involvement in angiogenesis and vascular remodelling. In this study, we examined the role of netrin‐1 in angiogenesis and explored the underlying mechanisms. The effect of netrin‐1 on brain tissues and endothelial cells was examined by immunohistochemistry and western blotting in a middle cerebral artery occlusion model and in human umbilical vein endothelial cells. Cell proliferation and cell cycle progression were assessed by the MTT assay and flow cytometry, and the Transwell and tube formation assays were used to examine endothelial cell motility and function. Netrin‐1 up‐regulated CD151 and VEGF concomitant with the activation of focal adhesion kinase (FAK), Src and Paxillin in vitro and in vivo and the induction of cell proliferation, migration and tube formation in vitro . Silencing of CD151 abolished the effects of netrin‐1 on promoting cell migration and tube formation mediated by the activation of FAK/Src signalling. Netrin‐1 promoted angiogenesis in vitro and in vivo by activating the FAK/Src/Paxillin signalling pathway through a mechanism dependent on the expression of the CD151 tetraspanin, suggesting the existence of a netrin‐1/FAK/Src/CD151 signalling axis involved in the modulation of angiogenesis.